Reforming the agricultural sector of the Republic of Moldova: A vital imperative in the context of the amplification of geopolitical and climatic crises in the region - Viorel Turețchi; Tatiana Turețchi (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 14th Edition, 2023)
The negative impact of climatic order (critical insufficiency of atmospheric precipitation) from 2022, as well as the military conflict in Ukraine, continue to exert extraordinary pressure on the economic efficiency of the agricultural sector of the Republic of Moldova. At the same time, the massive reorientation of agricultural products from Ukraine to the markets of the European Union, executed also through the transit of the territory of our country, created favorable conditions for domestic economic agents to re-export agricultural products of Ukrainian origin. Consequently, this fact further reduced the export capacity of Moldovan agricultural production. Adding to these factors the traditional low level of productivity but obtained at quite high costs, we have reached a situation where the given sector requires a radical reformation, a change to face the current challenges as well as those of the future.
Keywords: R23; Q15; Q18; 330; Agricultural sector; economic efficiency; reformation